Analysis of Higher Dimensional Converter Using Graphical Approach - J. Divya Navamani; K. Boopathi; M. Jagabar Sathik; A. Lavanya; Kitmo; Pradeep Vishnuram (IEEE Access, 2023)
The main intention of this paper is to propose a methodology for deriving a reduced-order model from a complex n-dimensional system. The mathematical model for a voltage-lift-based quadratic high-gain dc-dc converter is proposed with a reduced-order model in continuous conduction mode (CCM). The chosen topology amalgamates voltage-lift cells with a quadratic boost topology to obtain improved voltage gain. The operating principle of the configuration with steady-state analysis is discussed in CCM. The state-space averaging procedure and switching flow graph (SFG) obtain the open-loop performance to design a suitable controller for the converter. To reduce the state variables and simplify the modelling, reduced-order modelling is carried out for the topology. Additionally, the pole clustering method minimizes the converter’s order. The impact of parameter variation with the pole-zero location is discussed elaborately. The Ziegler-Nicholas tuning technique attains the PI controller’s proportional and integral time constant. The closed-loop response presents better step response output than the open-loop response. Time-domain parameters are compared for open-loop and closed-loop to validate the controller. Lastly, a 50 W prototype is used for evaluating the converter’s ability at a steady state.